(untitled) (Altre Modernità, 2024)
Vera Gheno, Femminili Singolari +: il femminismo è nelle parole, Firenze, effequ, 2021, 191 pp. ISBN 979-128-026-340-7 Sami Schalk, Bodyminds Reimagined (Dis)ability, Race, and Gender in Black Women’s Speculative Fiction, Durham and London, Duke University Press, 2018, 180 pp. ISBN 978-0-8223-7073-4